Revisiting the disjunct distribution of Conopleura Hinds, 1844 (Mollusca: Gastropoda: Drilliidae) - Nappo, Andrea; Rey, Xabier; Pellegrini, Daniel; Bonomolo, Giuseppe; Crocetta, Fabio (Zootaxa, 2018)
The family Drilliidae includes approximately 30 genera and 500 recent species. Among them, the genus Conopleura includes three recent species and shows a disjunct distribution in the central Indo-Pacific and the temperate northern Atlantic (Mediterranean Sea). Here, we review the genus, redescribe it, and investigate the validity of its accepted taxa by shell morphology and geometric morphometry. Conopleura striata and C. latiaxisa are considered as valid species. Their distribution has been enlarged to Taiwan and India for C. striata, and to Japan for C. latiaxisa. On the contrary, some discrepancies highlighted in the generic and familiar attribution of the Mediterranean species C. aliena suggested that it was established on abnormal shells of Tritia lima, a taxon of which C. aliena is considered a junior subjective synonym. This confutes the disjunct distribution of Conopleura. Based on a wide literature and material search on abnormalities in gastropods, we highlight the occurrence of a recurring aberration (here defined “Conopleura-like”) in gastropod shells that already led to the incorrect establishment of new taxa since early scientific observations.